Interfaith Marriage Between Human Right and State Law - Dhiyaul Habib Ifham; Rosnidar Sembiring; Utary Maharani Barus (Universitas Efarina, 2025)
Indonesia is not a religious country but Indonesia is also not a secular country, Indonesia does not make any religion the basis of the state, but all activities and behavior of Indonesian citizens cannot be related to religious matters. As this is supported by the first principle, namely